Flipping the Script: Description of Needs and Personality Traits of People Living with HIV in Malawi and Zimbabwe - Gumede-Moyo, Sehlulekile; Sharma, Sunny; Levy, Melissa; Ismail, Amir; Gadner, Cassie; Gwanzura, Cleorata; Nyirenda, Rose; Mkandawire, Philip; Chatora, Kumbirai; Poya, Ernest; Hasen, Nina (British Journal of Healthcare and Medical Research, 2024)
Effective HIV prevention programs require a combination of behavioral, biomedical and structural interventions. Behavior interventions address the cultural contexts within which risk behaviors occur and aim to stimulate uptake of HIV prevention services. This research seeks to understand the relationship between the underlying needs people living with HIV (PLHIV) have from treatment, their personality traits, and how it influences treatment behavior. The overall focus is to develop the most successful campaign across sub-Saharan Africa, but primarily in Malawi and Zimbabwe. This was a cross-sectional quantitative study where interviews with 786 adult PLHIV and 504 healthcare workers (HCWs) were conducted via Computer Assisted Telephone Interviewing (CATI) in Malawi and Zimbabwe. PLHIV in Malawi and Zimbabwe are typically adherent to their medication. For PLHIV the power of the pill is scary and controlling but also liberating. Early associations with HIV tend to derive from negative comments being made about PLHIV, which fosters a sense that PLHIV are not accepted by the wider community. HCWs in Malawi and Zimbabwe do prioritize emotional support but have limited capacity to provide wider pastoral care. PLHIV, and HCWs, have good awareness of what viral suppression is, but do not always understand what it truly means. Utilization of communication channels that are acceptable and trusted will be key to successful HIV literacy treatment campaigns.